2021
DOI: 10.3389/fcimb.2021.752011
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the Conjugative Virulence Plasmid From a CG23 Hypervirulent Klebsiella pneumoniae Strain Enhances Bacterial Virulence

Abstract: The emergence of hypervirulent and carbapenem-resistant Klebsiella pneumoniae (hv-CRKP) has become a hot topic and confounding problem for clinicians and researchers alike. Conjugative virulence plasmids have the potential to cause more threatening dissemination of hv-CRKP strains. We previously identified K2606, a CG23 clinical hypervirulent strain of Klebsiella pneumoniae harboring a conjugative virulence plasmid designated pK2606. In this study we examined hypervirulence levels using assays of biofilm forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…In addition to the resistance elements, we also observed that a key virulent factor, the iutA-iucABCD operon, was coharbored with armA , bla TEM-1B , aac(3)-IId , dfrA12 , aadA2 , sul1 , msr(E) , mph(E) , q nrB4 , and bla DHA , on the p1864-1 plasmid ( K. pneumoniae 1864). We also detected the siderophore production of K. pneumoniae 1864 and 1632 to determine the virulence contribution of the iutA-iucABCD operon, which was highly related to K. pneumoniae virulence phenotype ( 14 ), in K. pneumoniae 1864. We found a significant increase of siderophore production in K. pneumoniae 1864, compared with 1632, which did not harbor the iuc operon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the resistance elements, we also observed that a key virulent factor, the iutA-iucABCD operon, was coharbored with armA , bla TEM-1B , aac(3)-IId , dfrA12 , aadA2 , sul1 , msr(E) , mph(E) , q nrB4 , and bla DHA , on the p1864-1 plasmid ( K. pneumoniae 1864). We also detected the siderophore production of K. pneumoniae 1864 and 1632 to determine the virulence contribution of the iutA-iucABCD operon, which was highly related to K. pneumoniae virulence phenotype ( 14 ), in K. pneumoniae 1864. We found a significant increase of siderophore production in K. pneumoniae 1864, compared with 1632, which did not harbor the iuc operon.…”
Section: Resultsmentioning
confidence: 99%
“…The chrome azurol S (CAS) assay was performed as previously described to determine the iron-chelating capabilities of bacterial supernatants ( 14 ). Briefly, the stationary-phase iron-chelated cultures (10 μL) were dropped on CAS plates, and siderophore production was determined by the orange halos after incubation for 48 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The relative quantitative siderophore production was assayed via Chrome Azurol S (CAS) Assay as described in our previous study [ 30 ]. Siderophore units (Su) were used to quantify the siderophore production [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…G. mellonella larvae used in this study weighed about 200∼400 mg and were purchased from the Tianjin Huiyude Biotech Company. The infection experiments were performed as described in our previous study [ 30 ], except that the bacterial inoculum employed was adjusted to 1×10 5 CFU. The experiments were repeated three times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation